10+6q=14+5q

Simple and best practice solution for 10+6q=14+5q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10+6q=14+5q equation:


Simplifying
10 + 6q = 14 + 5q

Solving
10 + 6q = 14 + 5q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '-5q' to each side of the equation.
10 + 6q + -5q = 14 + 5q + -5q

Combine like terms: 6q + -5q = 1q
10 + 1q = 14 + 5q + -5q

Combine like terms: 5q + -5q = 0
10 + 1q = 14 + 0
10 + 1q = 14

Add '-10' to each side of the equation.
10 + -10 + 1q = 14 + -10

Combine like terms: 10 + -10 = 0
0 + 1q = 14 + -10
1q = 14 + -10

Combine like terms: 14 + -10 = 4
1q = 4

Divide each side by '1'.
q = 4

Simplifying
q = 4

See similar equations:

| 37-6x=61-2x | | -3(6y-7)-y=-3(y-2) | | 5x^9*2u*2u^2x^9= | | 7(7n+3)-10(n-9)= | | 3/10t=6 | | y-13=-4 | | 0=8r-3r | | 2(a+1)=3(a-2)-a | | 3m+6=-6+m | | 10+m/2=6 | | q=-45/-3 | | 2(x+4)-5(x-3)=34 | | 6x-6-8=4x-4+6-2x | | 8+7x=78 | | 5n+7n=-12 | | 6+15y-3=8y+107-6y | | 5(a-12)-24=3(s+2) | | 5x-7-3x=19 | | (8t+30)+(-2-16)=-22 | | (x-5)/(2)=(x+2)/(3) | | (-11)(-15)=y | | 7p-5(3+p)= | | 6.42-10d=25 | | 6x^2+45x=180 | | 2(3t-8)-4t=2 | | -x-12=45 | | 1-8m=-5m+16 | | 8a-4-4a=6-a | | 3x-11=30 | | x/2+2/3=3/4 | | v=x(25-2x)(12-2x) | | 7p-5(3+p)=7p-15-5p |

Equations solver categories